Normalisation of non-compliance of regulations: when do unclear responsibilities at workplace become a crime? : A case study about a safety crime at workplace - Niskanen, Verna (My University, 2025)
This study deals with the topic of safety crimes, using a fairly recent occupational safety crime case from Finland as an example. The study examines the case through a method of case study. The case concerns neglect of occupational safety in a company struggling with financial challenges. The case in many aspects represents a typical Finnish occupational safety crime, in which systematic and continuous neglect of occupational safety issues led to an employee’s injury and, in this case, death. I examine what factors in this case led to the lack of clarity on safety issues. Secondly, I try to elucidate how this lack of clarity in division of responsibility ultimately contributed to the incident that caused the death of one of the employees. I establish a connection and illustrate how strain theory explains the actions of the company and what the consequences were in the case. The strain theory helps to understand, what kind of factors can influence safety violations at workplace. The theory argues that companies can also resort to illegal actions in their operations in situations where they see no legal means to resolve the situation. The key-finding of this case study is that some of the more serious safety crimes in Finland are ultimately caused by bigger structural problems in organisations. Challenges within a company can create conditions for serious consequences if they are allowed to continue long enough. The ambiguous division of responsibilities within the company is clearly connected to the weak financial situation of the company. This case points out how important a clear division of responsibilities is in ensuring the occupational safety required by law. This thesis is based on a seminar paper collaboratively written by several students in a course titled Corporate Crime, Law and Power.

Tämä tutkimus käsittelee työturvallisuusrikoksia käyttäen esimerkkinä erästä suhteellisen hiljattain tapahtunutta työturvallisuusrikostapausta Suomesta. Tapauksessa on kyse työturvallisuuden laiminlyönnistä taloudellisten haasteiden kanssa kamppailleessa yrityksessä. Tapaus ilmentää monelta osin tyypillistä suomalaista työturvallisuusrikosta, jossa työturvallisuuskysymysten systemaattinen ja jatkuva laiminlyönti johti työntekijän loukkaantumiseen ja tässä tapauksessa myös kuolemaan. Tutkin työssäni, mitkä tekijät tässä tapauksessa johtivat epäselvyyteen turvallisuusasioihin liittyen. Toiseksi pyrin selvittämään, kuinka tämä vastuunjaon epäselvyys lopulta vaikutti tähän esimerkkitapaukseen, joka aiheutti yhden työntekijän kuoleman. Luon yhteyden ja havainnollistan sitä kautta, kuinka paineteoria selittää tässä tapauksessa yrityksen toimintaa ja mitä seurauksia sillä oli. Paineteoria auttaa ymmärtämään, minkälaiset tekijät voivat vaikuttaa turvallisuusrikoksiin työpaikalla. Teorian mukaan myös yritykset voivat turvautua toiminnassaan lainvastaisiin tekoihin sellaisissa tilanteissa, joissa ne eivät näe laillisia keinoja tilanteen ratkaisemiseksi. Tämän tapaustutkimuksen keskeinen havainto on, että osa Suomen vakavimmistakin työturvallisuusrikoksista johtuu viime kädessä organisatorisista ongelmista. Haasteet yrityksen sisällä voivat luoda olosuhteet vakavillekin seurauksille, mikäli niiden annetaan jatkua tarpeeksi pitkään. Yrityksen epäselvä vastuunjako on tapauksessa vahvasti yhteydessä sen heikkoon taloudelliseen tilanteeseen. Tapaukesta voidaan todeta kuinka tärkeää selkeä vastuunjako on lain edellyttämän työturvallisuudesta huolehtimisen kannalta. Tutkielma perustuu seminaarityöhön, joka on kirjoitettu yhdessä useamman muun opiskelijan kanssa kurssilla Corporate Crime, Law and Power.
Keywords: corporate crime, safety crime, white-collar crime, strain theory, corporate crime, turvallisuusrikos, yritysrikollisuus, paineteoria